PENGARUH PENGALAMAN KERJA, JAM KERJA, DAN MASA KERJA TERHADAP PENDAPATAN PEKERJA FORMAL PT. X SURABAYA - Setiawan, David; Ida Aju Brahma Ratih (Nirta Learning Centre, 2025)
This study aims to analyze the influence of work experience, working hours, and tenure on the income of formal workers at PT X. A quantitative approach was employed, using a survey method through questionnaires distributed to 53 respondents selected using simple random sampling. The collected data were analyzed using multiple linear regression. The results revealed that tenure significantly affects income, while work experience and working hours do not show significant effects individually. However, all three variables have a significant simultaneous effect on income. These findings provide insights for the company’s management in developing strategies to improve employee income. Keywords: Work experience, working hours, tenure, income, PT X